A user-friendly automatic toolbox for hand kinematic analysis, clinical assessment and postural synergies extraction - Lapresa, Martina; Zollo, Loredana; Cordella, Francesca (Frontiers in Bioengineering and Biotechnology, 2022)
The clinical assessment of the human hand is typically conducted by means of questionnaires or tests that include objective (e.g. time) and subjective (e.g. grasp quality) outcome measures. However, there are other important indicators that should be taken into account to quantify grasp and movement quality in addition to the time needed by a subject to execute a task, and this is essential for both human and artificial hands that attempt to replicate the human hand properties. The correct estimation of hand kinematics is fundamental for computing these indicators with high fidelity, and a technical background is typically required to perform this type of analysis. In addition, to understand human motor control strategies as well as to replicate them on artificial devices, postural synergies were widely explored in recent years. Synergies should be analyzed not only to investigate possible modifications due to musculoskeletal and/or neuromuscular disorders, but also to test biomimetic hands. The aim of this work is to present an open source toolbox to perform all-in-one kinematic analysis and clinical assessment of the hand, as well as to perform postural synergies extraction. The tool takes as input marker positions recorded with a motion capture system and automatically performs i) hand kinematic analysis; ii) clinical assessment, by computing meaningful performance indicators that can be used to quantify movement quality, and iii) postural synergies extraction and analysis. Two illustrative examples are described to demonstrate the applicability of the toolbox. It allows calculating joint angles with high accuracy and automatically performing clinical assessment and postural synergies extraction. Results can be visually inspected, and data can be saved for any desired post processing analysis. The tool can be easily exploitable in clinical contexts, as it does not require any particular technical knowledge to be used. In addition, it can be integrated with the SynGrasp toolbox to perform grasp analysis of underactuated virtual hands based on postural synergies.